Fish physiology - Hoar, W.S; Randall,D.J (Academic Press, 1969)
v. 1. Excretion, ionic regulation, and metabolism -- v. 2. The endocrine system -- v. 3. Reproduction and growth, bioluminescence, pigments, and poisons -- v. 4. The nervous system, circulation, and respiration -- v. 5. Sensory systems and electric organs -- v. 6. Environmental relations and behavior